Changes in pain and insulin-like growth factor 1 in fibromyalgia during exercise: the involvement of cerebrospinal inflammatory factors and neuropeptides - Bjersing, Jan L (BioMed Central, 2012)
INTRODUCTION: Fibromyalgia (FM) is characterized by chronic pain. Impaired growth hormone responses and reduced serum insulin-like growth factor 1 (IGF-1) are common in FM. The aim was to examine changes in serum IGF-1, cerebrospinal fluid (CSF), neuropeptides, and cytokines during aerobic exercise in FM patients. METHODS: In total, 49 patients (median age, 52 years) with FM were included in the study. They were randomized to either the moderate- to high-intensity Nordic Walking (NW) program (n = 26) or the supervised low-intensity walking (LIW) program (n = 23). Patients participated in blood tests before and after 15 weeks of aerobic exercise. Changes in serum levels of free IGF-1, pain rating on a 0- to 100-mm scale, pain threshold, and 6-minute walk test (6MWT) were examined. CSF, neuropeptides, matrix metalloproteinase 3 (MMP-3), and inflammatory cytokines were determined. Nonparametric tests were used for group comparisons and correlation analyses. RESULTS: Serum free IGF-1 levels did not change during 15 weeks of exercise between the two groups, although the 6MWT significantly improved in the NW group (p = 0.033) when compared with LIW. Pain did not significantly change in any of the groups, but tended to decrease (p = 0.052) over time in the total group. A tendency toward a correlation was noted between baseline IGF-1 and a decrease of pain in response to exercise (r = 0.278; p = 0.059). When adjusted for age, this tendency disappeared. The change in serum free IGF-1 correlated positively with an alteration in CSF substance P (SP) levels (r(s )= 0.495; p = 0.072), neuropeptide Y (NPY) (r(s )= 0.802; p = 0.001), and pain threshold (r(s )= 0.276; p = 0.058). Differing CSF SP levels correlated positively to a change in pain threshold (r(s )= 0.600; p = 0.023), whereas the shift in CSF MMP-3 inversely correlated with an altered pain threshold (r(s )= -0.569; p = 0.034). CONCLUSIONS: The baseline level of serum free IGF-1 did not change during high or low intensity of aerobic exercise. Changes in IGF-1 correlated positively with a variation in CSF SP, NPY, and pain threshold. These data indicate a beneficial role of IGF-1 during exercise in FM. Trial registration: ClinicalTrials.gov NCT00643006.